DIFFERENCES IN THE WORK ETHIC OF TEACHERS WHO TEACH IN STATE SCHOOLS AND TEACHERS IN PRIVATE SCHOOLS AT SMA N 2 LENGAYANG AND SMK TECHNOLOGY LENGAYANG - Widia Suci Rahmadani; Kurniawan, Rizal (Causalita, 2024)
This study aims to see how the work ethic of teachers who teach in state schools differs from teachers in private schools at SMA N 2 Lengayang and SMK Technology Lengayang. This study uses quantitative methods with a comparative quantitative design. The population in this study is teachers in state schools and teachers in private schools. The sampling technique in this study used a purposive sampling technique. This study has a sample of 60 teachers with details of 30 samples coming from SMA N 2 Lengayang and 30 samples from SMK Technology Lengayang. The instrument used in this study is the work ethic scale developed by Ngalia (2011) with a total of 27 items. This instrument is based on aspects of the work ethic from Cherrington (1980) which has 3 aspects including: work as a moral obligation, high work discipline, and pride in the results of work. Analysis result using independent sample t-test. The results of the data analysis test show that Ho is rejected and Ha is accepted with a significance value (2-tailed) of 0,048 < 0,05 which means that there is a difference in the work ethic of teachers who teach in state schools and teachers in private schools, where teachers in private schools have a higher work ethic.